Streptococcus agalactiae mural infective endocarditis in a structurally normal heart - Nobuhiro Ariyoshi; Keisuke Miyamoto; Dennis T. Bolger (Greater Baltimore Medical Center, 2016)
A 38-year-old Caucasian man with uncontrolled diabetes mellitus type 2 was admitted with a 1-week duration of fevers, chills, and a non-productive cough. He had a left ischiorectal abscess 1 month prior to admission. Physical examination revealed caries on a left upper molar and a well-healed scar on the left buttock, but no heart murmur or evidence of micro-emboli. Blood cultures grew Streptococcus agalactiae. A transesophageal echocardiogram revealed a mobile mass in the right ventricle that attached to chordae tendineae without valvular disease or dysfunction. A computed tomography (CT) with contrast revealed the mass within the right ventricle, a left lung cavitary lesion, and a splenic infarction. He was initially treated with penicillin G for a week. Subsequently, ceftriaxone was continued for a total of 8 weeks. A follow-up CT showed no evidence of right ventricular mass 8 weeks after discharge. This is the first reported case of S. agalactiae mural infective endocarditis in a structurally normal heart.